The influence of user generated content on hotel sales: an Indian perspective. (8th February 2021) - Sharma, Himanshu; Aggarwal, Anu G.
Abstract : Purpose: Nowadays, various hotels and third party websites allow guests to express their stay experience in the form of textual content and ratings termed as user-generated content (UGC). This study aims to explore the influence of UGC along with the financial aspect on the sales of the hotel. This will help them in making efficient business decisions and revenue generation by realizing the requirements of the guests. The proposed model provides an insight into the theoretical and practical significance of the concerned explanatory variables to the hoteliers. Design/methodology/approach: This paper considers the number of rooms, six aspect ratings (room, cleanliness, location, service, value and sleep quality), review length and readability as the independent variables. Revenue per available room is taken as the dependent variable. Log-linear regression analysis is performed on a data set of 78 hotels situated in Delhi National Capital Region to validate the relationships. Moreover, the differential impact of hotel type on these exploratory variables is studied. Findings: Research findings show that along with the financial aspect, the UGC components also play a key role in generating sales for the hotels. It was further observed that the two hotel categories, i.e. luxury and budget have different natures and also the characteristics of luxury hotels overshadow those of budget. Originality/value: This study uses the textual content of the reviews along with the numerical ratings. This is a unique combination for studying sales of hotels according to the knowledge of authors, where earlier studies focused only on the financial aspects.